2006
DOI: 10.1063/1.2402941
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent elastic modulus of single electroactive polymer nanofibers

Abstract: The authors report for the first time the size dependency of the elastic modulus of well-aligned single polymeric nanofibers. The nanofibers were fabricated from electroactive polymers (EAPs) and had an ellipsoidal cross section because of impingement between a solid surface and a polymer jet during electrospinning. Although the EAPs had very weak mechanical properties in the bulk, the elastic modulus of single EAP nanofibers increased exponentially as the diameter of the EAP nanofibers decreased to diameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 30 publications
7
79
1
Order By: Relevance
“…These values of the elastic modulus were significantly higher than the PVA bulk modulus of 1.7 GPa [35].W e anticipated the elastic modulus of PVA fibers would increase continually as the diameter decreases below 150 nm. Similar size-dependent effects were observed for other electrospun polymer fibers [36,37] which could be attributed to the size increase of the supramolecular structure [36], consisting of aligned domains of the polymer chains. These results showed that the diameter onset of this size-dependent effect was polymer dependent.…”
Section: 2supporting
confidence: 60%
“…These values of the elastic modulus were significantly higher than the PVA bulk modulus of 1.7 GPa [35].W e anticipated the elastic modulus of PVA fibers would increase continually as the diameter decreases below 150 nm. Similar size-dependent effects were observed for other electrospun polymer fibers [36,37] which could be attributed to the size increase of the supramolecular structure [36], consisting of aligned domains of the polymer chains. These results showed that the diameter onset of this size-dependent effect was polymer dependent.…”
Section: 2supporting
confidence: 60%
“…An abrupt increase in the elastic modulus of PAMPS (poly-2-acrylamido-2-methyl-1-propanesulfonic acid) nanofibers 14 (see Fig. 12) and polypyrrole nanotubes (see Fig.…”
Section: Mechanical Properties Of Polymer Nanofibersmentioning
confidence: 99%
“…8 Polymer nanofibers are intrinsically different from common bulk in that they demonstrate size-dependent behavior, a wellknown phenomenon frequently observed in nano-objects. Experimental studies have demonstrated the effect of size on the mechanical and thermodynamic properties of nano-objects, as seen with the elastic moduli of hollow fibers 9 and electrospun nanofibers, [10][11][12][13][14] which sharply increase below a certain fiber diameter, as well as shifts in object melting temperatures. 15,16 Similarly, thickness and surface interactions of ultrathin polymer films (the film thickness is in the order of 2R g of a polymer chain, or less) highly influence their glass transition and melting temperatures, [17][18][19] polymer dynamics in the glassy state, 20 crystallization kinetics and degree of crystallinity, [21][22][23] phase behavior, 24 and morphology.…”
mentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17] Mechanical characterization techniques that have been developed to test individual polymer fibers include uniaxial tensile loading as well as bending and indentation of individual fibers using atomic force microscopy (AFM) cantilevered probes to impose deformation. For example, the effects of processing conditions on mechanical properties of electrospun poly(L-lactide) (PLLA) nanofibers with diameters of 610 and 890 nm were investigated via tensile testing.…”
Section: Introductionmentioning
confidence: 99%